The Oldest Known Tentaculitid: From the Chepultepec Limestone (Canadian) of Virginia - Fisher, D. W.; Young, R. S. (Journal of Morphology, 1955)
A new tentaculitid, Tentaculites lowdoni Fisher & Young, n.sp., is described and illustrated from the Lower Ordovician (Canadian) Chepultepec limestone, near Fishersville, Augusta County, Virginia. This discovery is of significance as it extends the stratigraphic range of the Tentaculitidae; the lower limit previously being considered Middle Ordovician (Trentonian).
Keywords: paleontology